The role of succinate dehydrogenase in the Drosophila melanogaster intestinal stem cells and tissue homeostasis - Costa, Ricardo André Baptista Pereira da (2019)
Adult stem cells maintain tissue homeostasis and act in response to challenges such as infection or mechanical damage. The fruit fly Drosophila melanogaster has emerged as a powerful model to study adult stem cells due to its conserved pathways and the existence of different stem cell systems, particularly a stem cell niche in the intestine. Intestinal stem cells (ISCs) have a major role in maintaining tissue homeostasis and improvements in their function result in refined tissue function in aged or damaged organs. Metabolism plays an important role in regulating stem cell activity, influencing cellular events such as differentiation and proliferation. However, several aspects remain unraveled, particularly the role of different subunits of the mitochondrial electron transport chain (ETC) — end players in the oxidative phosphorylation process. Given the importance of metabolism in regulating stem cell activity, we hypothesized that ETC subunits also have a role in regulating ISC activity and tissue homeostasis. To test our hypothesis, we performed a candidate screen to knock down individual subunits of the ETC specifically in ISCs and their direct progeny — enteroblasts — in the adult fly and studied their requirements for normal cell division, differentiation, survival and impact in surrounding differentiated cells. Subunits of the ETC complex II, which converts succinate to fumarate in the Krebs cycle, particularly subunit D (SdhD), emerged from the screen as strong candidates required for normal ISC activity. Knockdown of SdhD in ISCs resulted in inhibition of cell division, hypertrophy with polyploidy, and ultimately, cell death. At a tissue level, evidence of a differentiation bias towards secretory enteroendocrine cells in lieu of absorptive enterocytes was observed upon SdhD knockdown in progenitor cells. Further experiments showed that knockdown of SdhD causes succinate to accumulate, possibly due to a decrease in the function of succinate dehydrogenase activity. Succinate is a known ligand for the GPR91 receptor in mammals which is known to be involved in cellular hypertrophy and death via apoptosis. Further studies need to be performed to determine the existence of a succinate receptor in Drosophila. This work has unveiled a direct relationship between inhibition of complex II subunits and stem cell hypertrophy and death, with succinate as a possible intermediate, and provides a suitable model for the study of the molecular pathways underlying cellular hypertrophy and death in metabolic-deficiency backgrounds. These insights may contribute to the understanding of hypertrophic pathologies, or proliferative diseases, such as cancer.